A Study on Impact of Brand Equity on Consumer Buying Pattern of Instant Food Products (IFPS) In Pune City. - Yogendrah Deaokar (European Economic Letters (EEL), 2024)
The food sector currently accounts for the majority of the food energy consumed by people worldwide. Organizations including the Food and Agriculture Organization, World Resources Institute, International Food Information Council, International Association for Food Protection and World Food Programmed keep an eye on food security and safety. Sustainability, biological diversity, climate change, nutritional economics, population growth, water supply, and food access are just a few of the issues they address, so it's critical to research how branded food brands affect consumer purchasing decisions. Research reveals that these decisions are strongly influenced by factors like taste, price, and availability of nearby locations, brand ambassadors, advertisements, and nutritional value. However the consumer buying behavior is characterized by supremacy of mass marketed brands and increased specialization in marketing of such brands. It is a combination of elements from psychology, sociology, social anthropology, marketing and economics. Eight well-known products were examined in this study: Nestle-Mggi, Knoor, Ching's Secret, Top Ramen.